The Effectiveness of Bio Activator of Phosphate Solubilizing Bacteria Consortium on Composting Bag-log Waste Incorporated with Cow Dung - Lolita Endang Susilowati; Mahrup Mahrup; Zaenal Arifin; R. Sutriono (Postgraduate, University of Mataram, 2023)
Bag-log waste is an organic material that is difficult to decompose. This is due to the bag log's high content of lignin compounds. Therefore, to speed up the composting process, it is necessary to include other organic materials and bio activators. This study aims to analyze the effectiveness of the bio-activator consortium of Phosphate Dissolving Bacteria (KBPF) in composting bag-log waste mixed with cow dung. The experiment consisted of 5 treatments with three replications, namely (T1) bag-log waste, (T2) a mixture of bag-log waste and cow manure with a composition of 1:2 (wt/wt), (T3) a mixture of bag-log waste and cow manure with 2:1 ( wt/wt), (T4) a mixture of bag-log waste and cow manure with a composition of 1:2 (wt/wt) plus KBPF (200 ml) with a density of 108 CFU/ml (T5) a mixture of bag-log waste and cow manure with a composition of 2:1 (wt/wt) plus KBPF (200 ml) with a density of 108 CFU/ml. The experiment was created as - Completely Randomized Design (CRD). The experimental results show that bag-log waste cannot be decomposed fastly without cow dung and bio activators. The treatments of T2, T3, T4 and T5 produced compost with quality not significantly different from one another. Under these treatments, the temperature was controlled in the mesophilic stage, and the composting pH was returned to neutral, while the moisture content and C/N ratio decreased to almost half of their original levels at the end of the composting period. It seems that inoculation of KBPF into the mixture of cow dung and bag-log waste has no role in accelerating the composting process. The mix of Bag-log and cow dung, with a minimal proportion of 2:1 without inoculation KBPF, was the recommended combination in composting bag-log in which the final product (compost) could fulfil its pH (neutral), the threshold of temperature and water content.Â The C/N ratio of the treatment was close C/N ratio of mature compost, and total N and total P contents were more than the standard of SNI 19-7030-2004.